Pengaruh Therapeutic Exercise Walking terhadap Sirkulasi Darah Perifer pada Pasien Diabetes Melitus Tipe 2 di Kelurahan Gebang Kecamatan Patrang Kabupaten Jember. (The Effect of Therapeutic Exercise Walking on Pheripheral Blood Circulation in Patients wit - Amadea Yollanda; Nur Widayati; Rondhianto Rondhianto (Pustaka Kesehatan, 2016)
Pathological change experienced by patients with type 2 diabetes mellitus is impaired peripheralblood circulation, especially in the lower limbs and feet. Peripheral blood circulation can be examinedby measuring Ankle Brachial Index (ABI). Therapeutic exercise walking is one of physical activitieswhich can improve blood circulation. This research goal was to analyze the effect of therapeuticexercise walking on peripheral blood circulation in patients with type 2 diabetes mellitus. Theresearch design was randomized control group pretest-posttest design. The sample size was 15respondents as control group and 15 respondents as treatment group. Data was analyzed by usingdependent t-test and independent t-test with significant level of 0.05. This result showed a significantincrease of ABI after therapeutic exercise walking in the treatment group (p= 0.001). However therewas a significant decrease of ABI between pretest and posttest in control group (p=0.010).Independent t-test indicated a significant difference of ABI between treatment group and controlgroup (p=0.000). So, it can be concluded that there is an influence of therapeutic exercise walking onthe peripheral blood circulation in patients with type 2 diabetes mellitus. Nurses should applytherapeutic exercise walking to improve peripheral blood circulation in patients with type 2 diabetesmellitus.Keywords: type 2 diabetes mellitus, therapeutic exercise walking, ankle brachial index